Chronic Inflammatory Demyelinating Polyneuropathy Following Natural Influenza A Infection in a Pediatric Patient: A Case Report and Literature Review - Grew, Emily; Gianneschi, Garrett; Elgallab, Janet (Case reports in neurological medicine, 2025)
Chronic inflammatory demyelinating polyneuropathy (CIDP) following viral infections and influenza vaccination has been well documented. However, there have been no confirmed natural influenza A infections leading to development of CIDP. Therefore, we present the case of a 6‐year‐old male who developed CIDP following a confirmed influenza A infection. Initially presenting with typical flu‐like symptoms, the patient experienced a gradual onset of gait instability and leg weakness approximately 1 month later. Despite initial improvement with intravenous immunoglobulin therapy following a diagnosis of Guillain–Barré syndrome, his symptoms relapsed, including lower extremity weakness, incontinence, and sensory loss. Electromyography confirmed a demyelinating polyneuropathy, leading to a diagnosis of CIDP.